Potential therapy of umbilical cord mesenchymal stem cells (UC-MSC) in renal fibrosis - Lusiana, Evi; Legiran, Legiran (Faculty of Medicine, Universitas Islam Sultan Agung (UNISSULA), Indonesia, 2023)
Renal fibrosis (RF) is a severe kidney pathology defined by myofibroblast anomalies that create extracellular material on the interstitial and glomerular surfaces. The current therapy for treating renal disease has not achieved excellent results. A new theory about applying umbilical cord mesenchymal stem cells (UC-MSC) to treat renal fibrosis and other fibrosis-affected organs has been developed. This review aims to elucidate the role of UC-MSC in the therapy of renal fibrosis and summarize the numerous biological mechanisms involved. A search was undertaken using PubMed and Google Scholar from 2003 to 2021 to gather information regarding the Potential therapy with UC-MSC in renal fibrosis. Multiple studies on rat models of renal fibrosis have demonstrated a considerable improvement in fibrotic kidneys following UC-MSC treatment. It can transfer functional proteins and genetic information to recipient cells that suppress the fibrosis process. UC-MSC is considered a superior approach to MSC for therapeutic purposes due to its straightforward collection, minimum immunogenicity, and solid paracrine potency. The UC-MSC cellular treatment for renal impairment is a feasible option in the future.